The Effects of Online Group Counseling Program Based on Mindfulness Based Cognitive Therapy to Enhance Resilience of Mothers of Children with Autism - Puttamon, Chanoknun; Surakarn, Amaraporn; Kramanon, Sittiporn (Manutsat Paritat: Journal of Humanities, 2022)
The purposes of this research were to compare the following; 1) the resilience of the mothers of autistic children in the experimental group before and after receiving an online group counseling program using mindfulness- based cognitive therapy; and (2) the resilience of the mothers of autistic children in the experimental group, who took a counseling program using mindfulness-based cognitive therapy and the control group who received a mindfulness handbook. The sample consisted of 30 mothers of children who were diagnosed with autism. According to the DSM-V diagnostic manual, children were aged 3-12 years, with their mothers as their primary caregivers, and who met the inclusion criteria. They were matched-pair by resilience score and then randomly assigned into experimental and control group with 15 subjects in each group. The research used a pretest-posttest quasi-experimental design. The research instruments were comprised of the following: (1) an online group counseling program based on mindfulness-based cognitive therapy; and (2) a Resilience Quotient (RQ). The data were analyzed using mean, standard deviation and a t-test. The major findings were as follows: (1) the resilience score of the mothers of autistic children after receiving the online group counseling program based on mindfulness- based cognitive therapy that was significantly higher than before at a level of 05; and (2) the resilience scores of the mothers of autistic children after receiving the online group counseling program using mindfulness-based cognitive therapy was significantly higher than those who received a mindfulness handbook at a level of .05.